Aplicación de la gobernanza del derecho administrativo y su impacto en la antinomia del derecho notarial. - Orellana Intriago, Fernando Rodolfo (2025)
The notarial function in Ecuador has been constitutionally recognized as a pillar of the justice system, essential for ensuring legal certainty. However, it faces significant challenges stemming from normative antinomies and a weak articulation with administrative law, which have affected its effectiveness and coherence. The general objective of this research was to analyze the Ecuadorian notarial system in relation to its role in consolidating legal certainty, considering normative conflicts and its connection with administrative governance. Methodologically, a qualitative-descriptive approach was employed, including legal review, doctrinal analysis, and comparative study with European and Latin American models. The results revealed that legal contradictions have generated ambiguities in the interpretation of notarial norms, affecting document authenticity, conflict prevention, and the guarantee of rights. Nevertheless, the integration of governance principles—such as efficiency, transparency, and citizen participation— along with process digitalization and notary training, emerged as effective strategies to overcome these limitations. At the comparative level, it was found that normative harmonization and reforms in countries such as Mexico, Argentina, and Colombia have strengthened the notarial role. In conclusion, strengthening the notarial system in Ecuador requires a comprehensive legal review and effective coordination with administrative law, within a framework of institutional modernization that promotes legal certainty and citizen trust.